Implementasi Metode 360 Derajat Pada Sistem Informasi Penilaian Kinerja Pegawai pada CV. Alfa Printing - Huda, Haris Ihsanil; Sudirman, Bagus; Aqham, Ahmad Ashifuddin (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2022)
Performance appraisal that is carried out properly will be beneficial for both employees and the company itself. The 360-degree assessment method is that an employee's assessment is not only taken from the assessment of his immediate supervisor or second superior above him, but also requested from an equal peer or from the relevant direct subordinate, the largest contribution of the assessment comes from his immediate supervisor and second supervisor. By applying the 360-degree method to the employee performance appraisal information system, it can eliminate the objectivity of the appraiser in assessing employee performance. By applying the 360-degree method to the employee performance appraisal information system, it makes it easier to assess employee data.